2018
DOI: 10.3354/dao03217
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing detection and co-detection of Ranavirus and Batrachochytrium dendrobatidis in Midwestern North American anuran populations

Abstract: Amphibian populations are in decline worldwide as they face a barrage of challenges, including infectious diseases caused by ranaviruses and the amphibian chytrid fungus Batrachochytrium dendrobatidis (Bd). Here we describe seasonal dynamics of Bd and ranavirus detection in free-ranging post-metamorphic wood frogs Lithobates sylvaticus, boreal chorus frogs Pseudacris maculata/triseriata, and gray treefrogs Hyla versicolor/chrysoscelis, sampled over a 3 season gradient in Minnesota (USA) wetlands. We detected B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Only recently, however, has there been a shift in focus towards understanding whether frog skin derived AMPs are antimicrobial to frog pathogens. Emerging infectious diseases continue to decimate worldwide amphibian populations and, pathogens, such as ranaviruses and Bd , are implicated as proximal causes in frog declines (139). It is critical to gain a further understanding of how to mitigate these diseases in order to conserve dwindling frog populations.…”
Section: Chemical Barriersmentioning
confidence: 99%
“…Only recently, however, has there been a shift in focus towards understanding whether frog skin derived AMPs are antimicrobial to frog pathogens. Emerging infectious diseases continue to decimate worldwide amphibian populations and, pathogens, such as ranaviruses and Bd , are implicated as proximal causes in frog declines (139). It is critical to gain a further understanding of how to mitigate these diseases in order to conserve dwindling frog populations.…”
Section: Chemical Barriersmentioning
confidence: 99%
“…Batrachochytrium dendrobatidis and ranaviruses, the most devastating parasites of amphibians [ 64 , 97 , 149 , 150 ], can co-occur [ 7 , 151 153 ] and cause repeated severe mass die-offs [ 154 ]. Although several studies have reported the co-infection of amphibians with Bd and Ranavirus under natural conditions [ 155 160 ] and captive populations [ 161 164 ], little information exists on within-host interactions between these agents.…”
Section: Co-infection By Heterologous Parasitesmentioning
confidence: 99%
“…as well [ 164 ]. Finally, elevated physiological stress periods, such as during breeding or when animals pass through sensitive developmental windows, may make amphibians temporally more vulnerable to co-infection [ 160 , 164 ].…”
Section: Co-infection By Heterologous Parasitesmentioning
confidence: 99%
See 2 more Smart Citations